Surface modification method of sodium-ion battery positive electrode material and sodium-ion battery positive electrode material
By modifying the surface of chlorosulfonic acid and liquid nitrogen on the positive electrode material of sodium ion battery, the problem of structural damage and performance decay during the charging and discharging process is solved, and the charging and discharging efficiency and cycle stability of the material are improved, making it suitable for large-scale production.
Patent Information
- Application Number
- CN202411788322.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-06
AI Technical Summary
During the charging and discharging of sodium ions, the structure damage and performance decline of sodium ions are caused by the insertion and disengagement of sodium ions. The existing sodium compensation additives have problems such as gas generation, serious residues and inappropriate oxidation potential, which affects energy density and cycling stability.
By mixing the nickel-ferromanganese hydroxide precursor with a sodium source ball mill and sintering under an oxidative atmosphere, the mixture powder was obtained and heat treated in a tube furnace. Then, chlorosulfonic acid and liquid nitrogen were added to the polytetrafluoroethylene container for surface modification, removing surface impurities and improving the interface characteristics of the material.
The modified sodium ion battery positive electrode material shows better charging and discharging efficiency and cycle stability, and is simple in process and low in cost, making it suitable for large-scale production.
Smart Images

Figure CN119660824A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sodium ion batteries, and in particular to a surface modification method of a positive electrode material of a sodium ion battery and a positive electrode material of a sodium ion battery. Background Art
[0002] Sodium-ion batteries have attracted widespread attention due to their low cost and abundant resources, becoming a potential alternative for large-scale energy storage, especially in the context of the growing demand for clean energy and sustainable development. Despite this, sodium-ion batteries still lag behind commercial lithium-ion batteries in terms of energy density and cycle life. During the charge and discharge process, the positive electrode material undergoes volume changes due to the insertion and extraction of sodium ions, which can easily lead to structural damage and performance degradation, resulting in sodium ion loss, thereby affecting energy density and cycle stability. Therefore, reducing Na + Losses are crucial for practical applications.
[0003] Introducing sodium compensation additives into the positive electrode is a direct and effective way to supplement Na + method. The ideal additive should meet the requirements of high capacity utilization, appropriate decomposition voltage and controllable gas release. Although a variety of sodium compensation additives such as Na2C4O4, Na2CO3, NaN3, etc. have been developed recently, many still face bottlenecks such as continuous gas generation, severe residues after decomposition and inappropriate oxidation potential, which hinder the improvement of energy density and bring safety hazards. Therefore, the development of effective sodium compensation measures is of great significance for the further industrialization of sodium-ion batteries.
[0004] Using layered oxides as sodium supplements for sodium-ion batteries can effectively improve performance, but their poor air stability is a major problem. When exposed to air, residual alkali is easily formed on the surface of layered oxides, which reduces the electrochemical activity. Therefore, effective surface treatment measures are needed to enhance their stability and improve their electrochemical performance. Through surface modification, such as coating a protective layer or chemical treatment, surface impurities can be removed and the interfacial properties of the material can be improved, thereby optimizing the performance of layered oxides in batteries and ensuring their reliability and durability in practical applications. Summary of the invention
[0005] In view of the above problems, the present invention provides a surface modification method of a sodium ion battery positive electrode material and a sodium ion battery positive electrode material, and uses chlorosulfonic acid and liquid nitrogen to modify the surface of the sodium ion battery positive electrode material, so as to solve the technical problem that residual alkali is easily formed on the surface of layered oxide and improve battery performance.
[0006] To achieve the above-mentioned purpose, the present application proposes the following technical solution: a surface modification method of a positive electrode material for a sodium ion battery, comprising the following steps:
[0007] S1. The nickel iron manganese hydroxide precursor is ball-milled and mixed with a sodium source, and then sintered in an oxidizing atmosphere to obtain a mixture powder, and the mixture powder is heat-treated in a tube furnace to obtain a positive electrode material;
[0008] S2. placing the obtained positive electrode material in a polytetrafluoroethylene container, adding chlorosulfonic acid, the amount of chlorosulfonic acid added is 1%-5% of the mass of the positive electrode material, reacting for 10-30 minutes to perform surface etching, and then immediately adding liquid nitrogen to react, the ratio of the amount of liquid nitrogen added to the amount of chlorosulfonic acid added is 1:1-1:1.5;
[0009] S3. After the liquid nitrogen is evaporated, the reaction mixture is taken out and washed, and then dried to obtain a surface-modified sodium ion battery positive electrode material.
[0010] Preferably, in step S1, the sodium source is selected from one or more of sodium carbonate, sodium bicarbonate, sodium citrate, sodium oxalate, and sodium acetate; the chemical formula of the nickel iron manganese hydroxide precursor is Ni a Fe b Mn c (OH)2, wherein 0<a≤1, 0<b≤1, 0<c≤1, and the molar ratio of the nickel-iron-manganese hydroxide precursor to the sodium source is 1:1.05-1:1.25.
[0011] Preferably, in step S1, the ball milling has a rotation speed of 300-600 rpm and a ball milling time of 8-10 h.
[0012] Preferably, in step S1, the heat treatment is to place the mixture powder at 400-500°C for 3-6 hours, then heat it to 750-950°C and keep it for 10-20 hours. The heating rate during the sintering process is 3-5°C / min and it is carried out in an oxygen atmosphere.
[0013] Preferably, the nickel-iron-manganese hydroxide precursor is prepared by a co-precipitation method.
[0014] Preferably, the method for preparing the nickel-iron-manganese hydroxide precursor comprises the following steps:
[0015] (1) introducing a mixed metal salt solution of nickel, iron and manganese, an alkali solution and an ammonia solution into a reaction kettle in parallel, heating and stirring, and performing a coprecipitation reaction to obtain a reaction slurry;
[0016] (2) After aging, solid-liquid separation, washing and drying the reaction slurry, a precursor material is obtained.
[0017] Preferably, in step (1), the temperature of the coprecipitation reaction system is controlled to be 60-80° C., the pH is 8-13, the stirring speed is 400-1000 r / min, and the ammonia concentration is 10-20 g / L.
[0018] The present invention provides a sodium ion battery positive electrode material obtained by the method.
[0019] The present invention also provides a sodium ion battery, which comprises the sodium ion battery positive electrode material obtained by the above method.
[0020] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects:
[0021] Preparation of NaNi by sintering a Fe b Mn c O2, after sintering, the positive electrode material is reacted with chlorosulfonic acid to eliminate residual alkali on the surface of the material after the furnace is cooled to the specified temperature, and then the degree of reaction with liquid nitrogen is controlled. The treatment with chlorosulfonic acid introduces moderate surface defects, increases active sites, and improves the electrochemical properties of the electrode material. The amount of chlorosulfonic acid added is 1% to 5% of the mass of the layered oxide material. At lower concentrations, chlorosulfonic acid mainly optimizes the surface properties of the material by removing surface impurities and introducing moderate defects, while at higher concentrations, the reaction intensity is significantly enhanced, which may cause excessive corrosion. Therefore, combined with liquid nitrogen cooling, the reaction process can be precisely controlled to adjust the intensity and depth of the reaction, accurately control the formation of surface defects, and avoid excessive damage to the material.
[0022] The modified sodium ion battery positive electrode material obtained by the present invention has more excellent charge and discharge efficiency and cycle stability, and the method has the advantages of simple process and low cost, and can meet the needs of large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the X-ray diffraction pattern of the sample prepared in Example 1;
[0024] Figure 2 This is a surface SEM image of the sample prepared in Example 1;
[0025] Figure 3 This is the cross-sectional SEM image of the sample in Example 1;
[0026] Figure 4 is the XPS graph of Ni 2p of Example 1;
[0027] Figure 5 This is a SEM image of the cross section of the sample prepared in Comparative Example 1;
[0028] Figure 6 Cyclic curves of batteries assembled with the positive electrode materials of Example 1 and Comparative Example 1 at a current density of 130 mA / g;
[0029] Figure 7This is the surface SEM image of the sample prepared in Comparative Example 2;
[0030] Figure 8 This is the X-ray diffraction pattern of the sample prepared in Comparative Example 2;
[0031] Fig. 9 This is a cycle curve diagram of a battery assembled with the positive electrode material prepared in Comparative Example 2 at a current density of 130 mA / g;
[0032] Fig.10 This is a cycle curve diagram of a battery assembled with the positive electrode material prepared in Example 2 at a current density of 130 mA / g;
[0033] Fig.11 This is a cycle curve diagram of a battery assembled with the positive electrode material prepared in Example 3 at a current density of 130 mA / g;
[0034] Fig.12 This is the XPS graph of Ni of the sample treated with sulfuric acid in Comparative Example 3;
[0035] Fig.13 This is the XPS graph of Ni of the sample treated with hydrochloric acid in Comparative Example 3;
[0036] Fig.14 This is a cycle curve diagram of a battery assembled with the positive electrode material prepared by sulfuric acid treatment in Comparative Example 3 at a current density of 130 mA / g;
[0037] Fig.15 This is a cycle curve diagram of a battery assembled with the positive electrode material prepared by hydrochloric acid treatment in Comparative Example 3 at a current density of 130 mA / g;
[0038] Fig.16 This is a cross-sectional SEM image of the sample prepared in Comparative Example 2;
[0039] Fig.17 This is the XPS graph of Ni of the sample prepared by treating with chlorosulfonic acid in Example 3. DETAILED DESCRIPTION
[0040] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present application will be further described below in conjunction with specific embodiments.
[0041] Example 1
[0042] (1) preparing a soluble mixed metal sulfate solution of nickel, iron and manganese according to a molar ratio of Ni:Fe:Mn=1:1:1, wherein the total molar concentration of metal ions of nickel, iron and manganese is 2.5 mol / L;
[0043] (2) preparing a 5 mol / L sodium hydroxide solution and a 6 mol / L ammonia solution;
[0044] (3) Adding the mixed metal salt solution, sodium hydroxide solution and ammonia water into the reactor in parallel, with flow rates of 1 L / h, 2 L / h and 0.5 L / h respectively, controlling the pH value to 10, the reaction temperature to 60°C, the stirring speed to 500 r / min, and the ammonia concentration to 15 g / L. When the addition of the mixed metal salt solution is completed, stop adding the sodium hydroxide solution and ammonia water at the same time, continue stirring, and stir and age the reaction for 10 hours before stopping the reaction;
[0045] (4) filtering the slurry obtained by the reaction, washing it with pure water for multiple times, and drying it in an oven at 120° C. to obtain a precursor material;
[0046] (5) The obtained precursor material and sodium carbonate were mixed at a molar ratio of 1:1.15. The ball milling speed was 400 rpm and the ball milling time was 8 h.
[0047] (6) After the ball milling is completed, the mixed powder is placed in a tube furnace at 400°C for 4 hours, then heated to 800°C and kept at this temperature for 12 hours. The heating rate during the sintering process is 5°C / min, and the heat treatment is performed in an oxygen atmosphere. The material obtained after sintering is a layered oxide material.
[0048] (7) The sintered material is placed in a polytetrafluoroethylene container, and chlorosulfonic acid is added immediately. The amount of chlorosulfonic acid added is 1% of the mass of the layered oxide material, and the reaction is continued for 25 minutes.
[0049] (8) After the reaction is completed, liquid nitrogen is added, and the ratio of the volume of liquid nitrogen added to the volume of chlorosulfonic acid added is 1:1.
[0050] (9) After the liquid nitrogen is evaporated, the obtained powder is the sample.
[0051] Figure 1 This is the X-ray diffraction pattern of the sample prepared in Example 1, which shows that the material has an O3 type structure. Figure 2 This is the SEM image of the sample prepared in Example 1. It can be seen that the positive electrode composite material is spherical and has strip cracks on the surface with a diameter of about 3 to 5 μm. The sample was etched by argon ion beam cross-sectional milling technology at an etching rate of 700 μm / h to obtain a sample cross section. The sample cross section was tested by SEM to obtain Figure 3 Cross-sectional SEM images, from Figure 3 It can be seen that there are no cracks inside the material. Figure 4 is the XPS graph of Ni 2p in Example 1, where Ni 3+ The proportion is 33.29%.
[0052] Comparative Example 1
[0053] (1) preparing a soluble mixed metal sulfate solution of nickel, iron and manganese according to a molar ratio of Ni:Fe:Mn=1:1:1, wherein the total molar concentration of metal ions of nickel, iron and manganese is 2.0 mol / L;
[0054] (2) preparing a 6 mol / L sodium hydroxide solution and an 8 mol / L ammonia solution;
[0055] (3) Adding the mixed metal salt solution, sodium hydroxide solution and ammonia water to the reactor in parallel, with flow rates of 1 L / h, 2 L / h and 0.5 L / h respectively, controlling the pH value to 11, the reaction temperature to 60°C, the stirring speed to 550 r / min, and the ammonia concentration to 15 g / L. When the addition of the mixed metal salt solution is completed, stop adding the sodium hydroxide solution and ammonia water at the same time, continue stirring, and stir and age the reaction for 12 hours before stopping the reaction;
[0056] (4) filtering the slurry obtained by the reaction, washing it with pure water for multiple times, and drying it in an oven at 120° C. to obtain a precursor material;
[0057] (5) The obtained precursor material and sodium carbonate were mixed at a molar ratio of 1:1.05. The ball milling speed was 500 rpm and the ball milling time was 10 h.
[0058] (6) After the ball milling, the mixture powder was placed in a tube furnace at 450 °C for 5 h, then heated to 850 °C and kept at that temperature for 15 h. The heating rate during the sintering process was 4 °C / min, and the heat treatment was carried out in an oxygen atmosphere.
[0059] (7) The sintered material is placed in a polytetrafluoroethylene container, and chlorosulfonic acid is added immediately, the amount of chlorosulfonic acid added is 3% of the mass of the layered oxide material, and the reaction is carried out for 15 minutes. The powder obtained after the reaction is completed is the sample. The material obtained after sintering is the desired layered oxide material.
[0060] Figure 5 This is a SEM image of the cross section of the sample prepared in Comparative Example 1. It can be seen from the figure that the positive electrode composite material is spherical with internal cracks with a diameter of about 3 to 5 μm. Compared with Example 1, it is shown that liquid nitrogen treatment is beneficial to inhibit further reaction of chlorosulfonic acid to avoid damage to the material structure.
[0061] The positive electrode materials prepared in Example 1 and Comparative Example 1 were respectively prepared into positive electrode sheets, and metallic sodium was used as the negative electrode, and button batteries were respectively assembled. The button batteries were subjected to charge and discharge tests at 25° C. in the voltage range of 2V to 4V.
[0062] Figure 6The cycle curves of the battery assembled with the positive electrode materials of Example 1 and Comparative Example 1 at a current density of 130 mA / g are shown in FIG. Figure 6 It can be seen that the cycle performance of the battery assembled with the positive electrode material prepared in Example 1 is better than that of the battery assembled with the positive electrode material prepared in Comparative Example 1. After 100 cycles, the battery assembled with the positive electrode material of Example 1 has a specific capacity of 99.7 mAh / g and a capacity retention rate of 91.1%; while the battery assembled with the positive electrode material of Comparative Example 1 has a specific capacity of 82.3 mAh / g and a capacity retention rate of only 73.6%. The above results show that the performance of the modified positive electrode material is significantly improved.
[0063] Comparative Example 2
[0064] (1) preparing a soluble mixed metal sulfate solution of nickel, iron and manganese according to a molar ratio of Ni:Fe:Mn=1:1:1, wherein the total molar concentration of metal ions of nickel, iron and manganese is 3.0 mol / L;
[0065] (2) preparing 5 mol / L sodium hydroxide solution and 8 mol / L ammonia solution;
[0066] (3) Adding the mixed metal salt solution, sodium hydroxide solution and ammonia water to the reactor in parallel, controlling the pH value to be 11, the reaction temperature to be 65°C, the stirring speed to be 500r / min, and the ammonia concentration to be 12g / L, and stopping the addition of sodium hydroxide solution and ammonia water when the addition of the mixed metal salt solution is completed, and continuing to stir, stirring and aging the reaction for 12h, and then stopping the reaction;
[0067] (4) filtering the slurry obtained by the reaction, washing it with pure water for multiple times, and drying it in an oven at 120° C. to obtain a precursor material;
[0068] (5) The obtained precursor material and sodium carbonate were mixed at a molar ratio of 1:1.20. The ball milling speed was 550 rpm and the ball milling time was 10 h.
[0069] (6) After the ball milling, the mixed powder was placed in a tube furnace at 500°C for 6 h, then heated to 950°C for 18 h. The heating rate during the sintering process was 3°C / min, and the heat treatment was performed in an oxygen atmosphere. After the sintering was completed, the mixture was cooled to room temperature to obtain a sample.
[0070] Figure 7 This is the surface SEM image of the sample prepared in Comparative Example 2. Fig.16 This is a cross-sectional SEM image of the sample prepared in Comparative Example 2. It can be seen from the image that the positive electrode composite material is spherical, has no cracks on the surface and inside, and has residual alkali spots on the surface with a diameter of about 3 to 5 μm. Figure 8This is the X-ray diffraction diagram of the sample prepared in Comparative Example 2. It can be seen from the figure that the obtained sample presents an O3 type structure and Na2CO3. Compared with Comparative Example 1, it is shown that chlorosulfonic acid can treat the residual alkali on the surface.
[0071] The positive electrode material prepared in Comparative Example 2 was prepared into a positive electrode sheet, and metallic sodium was used as the negative electrode, and button batteries were assembled respectively. The button batteries were subjected to charge and discharge tests at 25° C. in the voltage range of 2V to 4V. Fig. 9 This is a cycle curve of a battery assembled with the positive electrode material prepared in Comparative Example 2 at a current density of 130 mA / g. Fig. 9 It can be seen that within the voltage range of 2V to 4V, after 100 cycles, it has a specific capacity of 89.3mAh / g and a capacity retention rate of 86.4%. Comparing the cycle performance of the battery assembled with the positive electrode materials prepared in Example 1 and Comparative Example 2, it can be seen that the material performance that has not been treated with chlorosulfonic acid and liquid nitrogen is poor. The performance comparison between Comparative Example 1 and Comparative Example 2 shows that the surface residual alkali without electrochemical activity can be treated after chlorosulfonic acid treatment. However, because Comparative Example 1 is not treated with liquid nitrogen, chlorosulfonic acid further penetrates into the material, forming cracks that destroy the structural stability of the material, thereby reducing the electrochemical performance of the material.
[0072] Example 2
[0073] (1) preparing a soluble mixed metal sulfate solution of nickel, iron and manganese according to a molar ratio of Ni:Fe:Mn=4:4:2, wherein the total molar concentration of metal ions of nickel, iron and manganese is 3.0 mol / L;
[0074] (2) preparing 5 mol / L sodium hydroxide solution and 8 mol / L ammonia solution;
[0075] (3) Adding the mixed metal salt solution, sodium hydroxide solution and ammonia water to the reactor in parallel, with flow rates of 1 L / h, 2 L / h and 0.5 L / h respectively, controlling the pH value to 10, the reaction temperature to 70°C, the stirring speed to 600 r / min, and the ammonia concentration to 18 g / L. When the addition of the mixed metal salt solution is completed, stop adding the sodium hydroxide solution and ammonia water at the same time, continue stirring, and stir and age the reaction for 10 hours before stopping the reaction;
[0076] (4) filtering the slurry obtained by the reaction, washing it with pure water for multiple times, and drying it in an oven at 120° C. to obtain a precursor material;
[0077] (5) The obtained precursor material and sodium carbonate were mixed at a molar ratio of 1:1.05. The ball milling speed was 600 rpm and the ball milling time was 10 h.
[0078] (6) After the ball milling is completed, the mixed powder is placed in a tube furnace at 450°C for 5 hours, then heated to 900°C for 18 hours. The heating rate during the sintering process is 3°C / min, and the heat treatment is performed in an oxygen atmosphere. The material obtained after sintering is the desired layered oxide material.
[0079] (7) The sintered material is placed in a polytetrafluoroethylene container, and chlorosulfonic acid is added immediately. The amount of chlorosulfonic acid added is 3% of the mass of the layered oxide material, and the reaction is continued for 15 minutes.
[0080] (8) After the reaction is completed, liquid nitrogen is added, and the ratio of the volume of liquid nitrogen added to the volume of chlorosulfonic acid added is 1:1.3.
[0081] (9) After the liquid nitrogen is evaporated, the obtained powder is the sample.
[0082] The positive electrode material prepared in Example 2 was prepared into a positive electrode sheet, and metallic sodium was used as the negative electrode. The button batteries were respectively assembled into button batteries. The button batteries were subjected to charge and discharge tests at 25° C. in the voltage range of 2V to 4V.
[0083] Fig.10 This is a cycle curve of a battery assembled with the positive electrode material prepared in Example 2 at a current density of 130 mA / g. Fig.10 It can be seen that within the voltage range of 2V to 4V, after 100 cycles, the specific capacity is 103.6 mAh / g and the capacity retention rate is 95.3%.
[0084] Example 3
[0085] (1) preparing a soluble mixed metal sulfate solution of nickel, iron and manganese according to a molar ratio of Ni:Fe:Mn=4:4:2, wherein the total molar concentration of metal ions of nickel, iron and manganese is 3.0 mol / L;
[0086] (2) preparing 5 mol / L sodium hydroxide solution and 8 mol / L ammonia solution;
[0087] (3) Adding the mixed metal salt solution, sodium hydroxide solution and ammonia water to the reactor in parallel, with flow rates of 1 L / h, 2 L / h and 0.5 L / h respectively, controlling the pH value to 12, the reaction temperature to 75°C, the stirring speed to 700 r / min, and the ammonia concentration to 18 g / L. When the addition of the mixed metal salt solution is completed, stop adding the sodium hydroxide solution and ammonia water at the same time, continue stirring, and stir and age the reaction for 10 hours before stopping the reaction;
[0088] (4) filtering the slurry obtained by the reaction, washing it with pure water for multiple times, and drying it in an oven at 120° C. to obtain a precursor material;
[0089] (5) The obtained precursor material and sodium carbonate were mixed at a molar ratio of 1:1.20. The ball milling speed was 700 rpm and the ball milling time was 10 h.
[0090] (6) After the ball milling is completed, the mixed powder is placed in a tube furnace at 450°C for 4 hours, then heated to 950°C and kept for 20 hours. The heating rate during the sintering process is 5°C / min, and the heat treatment is performed in an oxygen atmosphere. The material obtained after sintering is the desired layered oxide material.
[0091] (7) The sintered material is placed in a polytetrafluoroethylene container, and chlorosulfonic acid is added immediately. The amount of chlorosulfonic acid added is 5% of the mass of the layered oxide material, and the reaction is carried out for 15 minutes.
[0092] (8) After the reaction is completed, liquid nitrogen is added, and the ratio of the amount of liquid nitrogen added to the amount of chlorosulfonic acid added is 1:1.5.
[0093] (9) After the liquid nitrogen is evaporated, the obtained powder is the sample.
[0094] The positive electrode material prepared in Example 3 was prepared into a positive electrode sheet, and metallic sodium was used as the negative electrode. The button batteries were respectively assembled into button batteries. The button batteries were subjected to charge and discharge tests at 25° C. in the voltage range of 2V to 4V.
[0095] Fig.11 This is a cycle curve of a battery assembled with the positive electrode material prepared in Example 3 at a current density of 130 mA / g. Fig.11 It can be seen that within the voltage range of 2V to 4V, after 100 cycles, the specific capacity is 98.1 mAh / g and the capacity retention rate is 91.2%. Fig.17 This is the XPS graph of the Ni sample used in Example 3. It can be seen from the figure that Ni 3+ The proportion is 31.36%. Comparing Example 1, Example 2 and Example 3, it can be seen that the optimal addition amount of chlorosulfonic acid is 3%.
[0096] Comparative Example 3
[0097] (1) preparing a soluble mixed metal sulfate solution of nickel, iron and manganese according to a molar ratio of Ni:Fe:Mn=4:4:2, wherein the total molar concentration of metal ions of nickel, iron and manganese is 3.0 mol / L;
[0098] (2) preparing 5 mol / L sodium hydroxide solution and 8 mol / L ammonia solution;
[0099] (3) Adding the mixed metal salt solution, sodium hydroxide solution and ammonia water to the reactor in parallel, controlling the pH value to 12, the reaction temperature to 75°C, the stirring speed to 700r / min, and the ammonia concentration to 18g / L, and stopping the addition of sodium hydroxide solution and ammonia water when the addition of the mixed metal salt solution is completed, and continuing to stir, stirring and aging the reaction for 10h, and then stopping the reaction;
[0100] (4) filtering the slurry obtained by the reaction, washing it with pure water for multiple times, and drying it in an oven at 120° C. to obtain a precursor material;
[0101] (5) The obtained precursor material and sodium carbonate were mixed at a molar ratio of 1:1.20. The ball milling speed was 700 rpm and the ball milling time was 10 h.
[0102] (6) After the ball milling, the mixture powder was placed in a tube furnace at 450 °C for 4 h, then heated to 950 °C and kept at that temperature for 20 h. The heating rate during the sintering process was 5 °C / min, and the heat treatment was carried out in an oxygen atmosphere.
[0103] (7) The sintered material is placed in a polytetrafluoroethylene container, and sulfuric acid or hydrochloric acid is added immediately. The amount of sulfuric acid or hydrochloric acid added is 3% of the mass of the layered oxide material, and the reaction is carried out for 15 minutes.
[0104] (8) After the reaction is completed, liquid nitrogen is added, and the ratio of the amount of liquid nitrogen added to the amount of sulfuric acid or hydrochloric acid added is 1:1.5.
[0105] (9) After the liquid nitrogen is evaporated, the obtained powder is the sample.
[0106] Fig.12 This is the XPS graph of the Ni sample treated with sulfuric acid in Comparative Example 3. It can be seen from the figure that Ni 3+ The proportion is 22.49%. Fig.13 This is the XPS graph of the sample Ni treated with hydrochloric acid in Comparative Example 3. It can be seen from the figure that Ni 3+ Compared with Example 1, the Ni 3+ The content of was increased, indicating that the samples treated with chlorosulfonic acid had more defects and more active sites.
[0107] Fig.14 This is a cycle curve of a battery assembled with the positive electrode material prepared by sulfuric acid treatment in Comparative Example 3 at a current density of 130 mA / g. Fig.14 It can be seen that in the voltage range of 2V to 4V, after 100 cycles, the material treated with sulfuric acid has a specific capacity of 96.7mAh / g and a capacity retention rate of 89.1%; Fig.15The cycle curve of the battery assembled with the positive electrode material prepared by sulfuric acid treatment in comparative example 3 at a current density of 130 mA / g is shown. The positive electrode material prepared by hydrochloric acid treatment has a specific capacity of 95.6 mAh / g after 100 cycles in the voltage range of 2V to 4V, and the capacity retention rate is 90.6%. By comparing Example 2 with Comparative Example 3, it can be seen that chlorosulfonic acid has the best effect on electrochemical enhancement.
[0108] The present invention relates to a surface modification method for a positive electrode additive for a sodium ion battery, specifically, surface treatment of a layered oxide positive electrode material by chlorosulfonic acid, and control of the degree of reaction by liquid nitrogen. The method effectively adjusts the surface structure and chemical properties of the material by etching with chlorosulfonic acid under a low temperature environment, thereby improving the electrochemical performance of the battery. The strong corrosiveness of chlorosulfonic acid can not only remove impurities on the surface of the material, but also increase active sites. By introducing appropriate surface defects, the treatment with chlorosulfonic acid can improve the electrochemical properties of the electrode material, thereby improving its charge and discharge efficiency and cycle stability in the sodium ion battery. This selective treatment ensures that the material optimizes the electrochemical reaction process while maintaining structural integrity and fully realizes its potential, while liquid nitrogen cooling can accurately control the reaction process and avoid excessive damage to the material. The treated layered oxide material exhibits higher charge and discharge efficiency and cycle stability as a positive electrode additive for sodium ion batteries, and is an effective means to improve the performance of electrode materials in the field of sodium ion batteries.
[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for surface modification of a sodium ion battery positive electrode material, characterized in that: The following steps are included: S1. The nickel iron manganese hydroxide precursor is ball-milled and mixed with a sodium source, and then sintered in an oxidizing atmosphere to obtain a mixture powder, and the mixture powder is heat-treated in a tube furnace to obtain a positive electrode material; S2. placing the obtained positive electrode material in a polytetrafluoroethylene container, adding chlorosulfonic acid, the amount of chlorosulfonic acid added is 1%-5% of the mass of the positive electrode material, reacting for 10-30 minutes to perform surface etching, and then immediately adding liquid nitrogen to react, the ratio of the amount of liquid nitrogen added to the amount of chlorosulfonic acid added is 1:1-1:1.5; S3. After the liquid nitrogen is evaporated, the reaction mixture is taken out and washed, and then dried to obtain a surface-modified sodium ion battery positive electrode material.
2. The method according to claim 1, characterized in that: In step S1, the sodium source is selected from one or more of sodium carbonate, sodium bicarbonate, sodium citrate, sodium oxalate, and sodium acetate; the chemical formula of the nickel iron manganese hydroxide precursor is Ni a Fe b Mn c (OH)2, wherein 0<a≤1, 0<b≤1, 0<c≤1, and the molar ratio of the nickel-iron-manganese hydroxide precursor to the sodium source is 1:1.05-1:1.
25.
3. The method according to claim 1, characterized in that: In step S1, the ball milling has a rotation speed of 300-600 rpm and a ball milling time of 8-10 h.
4. The method according to claim 1, characterized in that: In step S1, the heat treatment is to place the mixture powder at 400-500°C for 3-6 hours, then heat it to 750-950°C and keep it for 10-20 hours. The heating rate during the sintering process is 3-5°C / min and it is carried out in an oxygen atmosphere.
5. The method according to any one of claims 1 to 4, characterized in that: The nickel-iron-manganese hydroxide precursor is prepared by a coprecipitation method.
6. The method according to claim 5, characterized in that: The method for preparing the nickel-iron-manganese hydroxide precursor comprises the following steps: (1) introducing a mixed metal salt solution of nickel, iron and manganese, an alkali solution and an ammonia solution into a reaction kettle in parallel, heating and stirring, and performing a coprecipitation reaction to obtain a reaction slurry; (2) After aging, solid-liquid separation, washing and drying the reaction slurry, a precursor material is obtained.
7. The method according to claim 6, characterized in that: In step (1), the temperature of the coprecipitation reaction system is controlled to be 60-80° C., the pH is 8-13, the stirring speed is 400-1000 r / min, and the ammonia concentration is 10-20 g / L.
8. A sodium ion battery positive electrode material obtained by any method of claims 1-7.
9. A sodium ion battery, characterized in that: The invention comprises a sodium ion battery positive electrode material obtained by any method of claims 1-7.
Citation Information
Patent Citations
Manganese-contained material recovery and regeneration method
CN109897964A
Preparation method of novel lithium iron phosphate condensed state-solid state battery
CN116053465A
Preparation of polymer material, preparation of solid polymer electrolyte membrane, and solid polymer electrolyte type of fuel cell
JP2000080120A
Electrolytic method for the manufacture of chlorates
US3878072A